Can gold prices forecast the Australian dollar movements? - Apergis, Nicholas (Elsever, 2014)
This paper explores whether gold prices have a reliable out-of-sample relationship with the Australian dollar/US dollar nominal and real exchange rates using daily and quarterly data, respectively, spanning the period 2000–2012. Through an Error Correction Model (ECM), the empirical findings suggest that the out-of-sample predictive ability is strong and robust across short- and long-run horizons. The results could offer informational availability for monetary policymakers, hedge fund managers and international portfolio managers. They also provide additional support to the hypothesis that both markets are driven by the same information sets.